2008
DOI: 10.1007/s11596-008-0504-z
|View full text |Cite
|
Sign up to set email alerts
|

High glucose promotes the CTGF expression in human mesangial cells via serum and glucocorticoid-induced kinase 1 pathway

Abstract: The role of serum and glucocorticoid-induced kinase 1 (SGK1) pathway in the connective tissue growth factor (CTGF) expression was investigated in cultured human mesangial cells (HMCs) under high glucose. By using RT-PCR and Western blot, the effect of SGK1 on the CTGF expression in HMCs under high glucose was examined. Overexpression of active SGK1 in HMCs transfected with pIRES2-EGFP-S422D hSGK1 (SD) could increase the expression of phosphorylated SGK1 and CTGF as compared with HMCs groups transfected with pI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…GO analysis of DEGs with significant alternative splicing found that one of the enriched terms was the apoptotic signal pathway, indicating that the apoptotic pathway may be related to the alternative splicing of genes. Studies [8,9] have shown that PPIA may affect the occurrence and development of diabetes complicated with coronary artery disease by regulating alternative splicing of LHPP , [45] APH1A , [46] SERGEF , [47] NFX1 , [48] PCBP4 , BRD1 , [49] and ORAI3 [50] genes. By KEGG analysis, we found that DEGs with significant alternative splicing were enriched in MAPK signaling pathway, which is related to many important cellular physiological/pathological processes, such as cell growth, differentiation, stress response, and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis of DEGs with significant alternative splicing found that one of the enriched terms was the apoptotic signal pathway, indicating that the apoptotic pathway may be related to the alternative splicing of genes. Studies [8,9] have shown that PPIA may affect the occurrence and development of diabetes complicated with coronary artery disease by regulating alternative splicing of LHPP , [45] APH1A , [46] SERGEF , [47] NFX1 , [48] PCBP4 , BRD1 , [49] and ORAI3 [50] genes. By KEGG analysis, we found that DEGs with significant alternative splicing were enriched in MAPK signaling pathway, which is related to many important cellular physiological/pathological processes, such as cell growth, differentiation, stress response, and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…SGK1, as a signal hub of sodium transport, regulates various renal Na + transporters, such as epithelial sodium channel (ENaC), voltage-gated sodium channel (Nav1.5), sodium hydrogen exchanger 1/3 (NHE1 and NHE3), sodium chloride cotransporter (NCC), sodium chloride potassium cotransporter 2 (NKCC2), Na + /K + -ATPase and type A natriuretic peptide receptor (NPR-A) ( 4 , 51 , 52 ). Exposure to hyperglycemia can dramatically stimulate the expression and activity of SGK1 in proximal tubule cells and mesangial cells ( 53 , 54 ). Enhanced SGK1 potentiates the activity of ENaC, NCC, NKCC2 and Na + /K + -ATPase, thereby exerting a significant effect on Na + reabsorption and the occurrence of secondary hypertension ( 55 ).…”
Section: Sgk1 Exaggerates Hyperglycemia-induced Diabetic Complicationmentioning
confidence: 99%
“…Moreover, enhanced SGK1 transcript levels were observed in diabetic nephropathy [29], Rett syndrome, organ rejection, dialysis, wound healing, glomerulonephritis, liver cirrhosis, fibrosing pancreatitis, Crohn's disease, lung fibrosis and cardiac fibrosis [4, 30]. …”
Section: Transcriptional Sgk1 Regulationmentioning
confidence: 99%
“…As indicated above, SGK1 transcription is stimulated by excessive glucose concentrations and strong SGK1 expression has been observed in renal tissue of diabetic patients [4, 29]. …”
Section: Pathophysiological Role Of Sgk1 In Diabetesmentioning
confidence: 99%